Synthesis, structure and conformational mobility of tetra-substituted cyanomethoxy p-tert-butylcalix[4]arenes - D'Alessio, D.; Krause-Heuer, A.; Skelton, B.; Fraser, B.; Massi, Massimiliano; Ogden, Mark (Royal Society of Chemistry, 2016)
The syntheses and single crystal X-ray structure determinations of 5,11,17,23-tetra-tert-butyl-25,26,27,28-tetrakis(cyanomethoxy)calix[4]arene (partial-cone conformer), 5,11,17,23-tetra-tert-butyl-25,27-bis(diethylcarbamoylmethoxy)-26,28-bis(cyanomethoxy)calix[4]arene (cone and partial-cone conformers), 5,11,17,23-tetra-tert-butyl-25,26,27-tris(cyanomethoxy)-28-hydroxycalix[4]arene, and 5,11,17,23-tetra-tert-butyl-25-diethylcarbamoylmethoxy-26,27,28-tris(cyanomethoxy)calix[4]arene (cone conformer) are reported. The calixarenes are found to be conformationally mobile when heated in DMSO, favouring the partial-cone conformer at equilibrium. The tris-substituted cyanomethoxy derivative was found to assume the partial-cone conformation in the solid state. Attempts to convert nitrile groups to tetrazole moieties in derivatives containing both amide and nitrile groups were unsuccessful.